URGENSI PERAN AGEN PERUBAHAN BIROKRASI DALAM MENINGKATKAN KINERJA APARATUR SIPIL NEGARA KANTOR IMIGRASI KELAS I TPI KENDARI - Nur Laila Taslim; Bakhtiar Abbas; Ummy Kalsum (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The formulation of the problem of this research is how the urgency of the role of bureaucratic change agents in improving the performance of State Civil Apparatus Immigration Office Class I TPI Kendari. The purpose of this study was to determine the Urgency of the Role of Agents of Bureaucratic Change in Improving the Performance of Civil Servants of the Immigration Office Class I TPI Kendari. This type of research is descriptive qualitative in nature. Sources of research data are primary data and secondary data. Data collection techniques are in-depth interviews, literature studies and documentation. The results of the study show that the role of a change agent in an organization is very important in improving the performance of employees or employees. The roles of change agents at the Immigration Office Class I TPI Kendari include: 1) As a catalyst, that is, change agents provide confidence to all employees within their respective work units about the importance of changing work units towards a better work unit; 2) As a driver of change, namely the agent of change is tasked with encouraging and mobilizing employees to participate in changes towards a better work unit; 3) As a solution provider, namely a change agent tasked with providing alternative solutions to employees or leaders in the work unit environment who face obstacles in the process of changing the work unit towards a better work unit; 4) As a mediator, namely a change agent whose job is to help expedite the change process, especially solving problems that arise in the implementation of bureaucratic reform and fostering relationships between parties inside and outside the work unit related to the change process; and 5) As a liaison, namely the agent of change is tasked with connecting two-way communication between employees in the work unit environment and decision makers. The conclusion of the study is that the role of a change agent at the TPI Kendari Class I Immigration Office is very important in improving employee performance. Therefore it is hoped that this role can be increased.